2008
DOI: 10.1002/apj.165
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drop in three‐phase oil–water–gas horizontal co‐current flow: experimental data and development of prediction models

Abstract: Pressure-loss data are reported for three-phase oil-water-gas flow in horizontal pipes of 0.0259 and 0.0501 m i.d. The pressure profiles exhibited a maximum value above a critical gas rate, which progressively moved to higher oil ratios as the gas rate was increased due to increased turbulence within the system. The actual pressure-drop profiles obtained depended mainly on the flow regimes present within the system. As the pipe diameter was reduced, the pressure drop was observed to increase for the same flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The fluctuation of pressure drop has been observed between 0.4 to 0.6 (fo). Similar results have been reported in the literature, where the pressure drop increased during the phases inversion [10,14].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The fluctuation of pressure drop has been observed between 0.4 to 0.6 (fo). Similar results have been reported in the literature, where the pressure drop increased during the phases inversion [10,14].…”
Section: Resultssupporting
confidence: 92%
“…Thus, the life of the pipe system would reduce. On the other hand, if the oil is the continuous phase, the effective viscosity of the liquid mixture would increase, which would increase the pressure drop, thereby, resulting in the increase in the energy requirement of the system [10,11]. The increase or decrease in the water cut can change the continuous liquid phase to the dispersed phase and vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test section in this facility was a stainless steel pipe that was 38 m long and had a 77.92 mm internal diameter. A further study was reported by Spedding et al [42] (see bottom-left frame of Figure 13). The oil properties for the 0.0259 m ID facility were ρ 0 = 828.5 kg m −3 and µ 0 = 0.0122 kg m −1 s −1 , while, for the 0.0501 m ID apparatus, they were ρ 0 = 854.2 kg m −3 and µ 0 = 0.0395 kg m −1 s −1 , all at 24 • C. However, their results do not show the phenomenon observed in the present work, where the pressure drop for the air-water flow is higher than for the air-oil flow.…”
Section: Comparison With Literature Datamentioning
confidence: 53%
“…The phenomena become more complicated with the addition of more phases to the flow. The bend affects the local phase velocities and relative position of each phase. , The interrelationship of centrifugal and gravitational forces is important owing to the difference in the densities of fluids. Furthermore, the slip between the fluids increases due to the separation created by the centrifugal force. , The flow orientation influences the relative position of fluids .…”
Section: Introductionmentioning
confidence: 99%